Potensi Wellness Tourism di Destinasi Ekowisata Mangrove Munjang: Memperkenalkan Forest Bathing Sebagai Alternatif Kegiatan Wisata Baru - Hardyanti; Bagas Anggara; Arinta Destri Larasati (Jurnal Penelitian Ilmu Pariwisata, 2025)
This study introduces the potential of health tourism, namely forest bathing as one of the alternative tourism activities that can be applied by the community to increase the economic independence of the community around the Munjang mangrove forest ecotourism. The Munjang mangrove area in harmony with the natural landscape is very supportive of the implementation of forest bathing. In addition, it is hoped that the mangrove ecotourism view can be an option for the development of Health ecotourism in Indonesia. This study uses a qualitative method through a case study approach in Munjang mangrove ecotourism with field observations, literature reviews and interviews. The results of this study introduce that Munjang mangrove ecotourism, namely mangrove forests that are right for forest bathing activities based on forest bathing elements according to the Qing Li 2018 book guide, has met the standards of tourism wellness activities and is supported by special stakeholders in the local community who manage Munjang destinations and map out tracking routes including short routes and long routes to support fitness tourism activities in addition to being an alternative to increasing local economic welfare and strengthening the recognition of the benefits of tourism wellness and providing a new nuance for Munjang mangrove destinations that carry the eco-wellness concept.